2009
DOI: 10.1017/s0260210509008596
|View full text |Cite
|
Sign up to set email alerts
|

Variegated neo-liberalism: transnationally oriented fractions of capital in EU financial market integration

Abstract: This article develops a twofold critique: on the one hand it addresses those accounts commonly associated with the Varieties of Capitalism literature and their associated understanding of neo-liberalism to argue that there is a dominant tendency to collapse into a binary analysis that asserts either we are witnessing convergence or we are experiencing path dependency. On the other hand it addresses 'neo-Gramscian' accounts which tend to overemphasise processes of transnational convergence and the emergence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 1 publication
1
29
0
3
Order By: Relevance
“…The transnationalisation of capital thesis has been popular among students of globalisation (Carroll, 2010;Carroll et al, 2010;Robinson, 2004;Sklair, 2001), but it has also generated critical debate that has shown that it should not be exaggerated, as domestic and international elites are not homogenous and national dominant classes have not lost all ties to their home country, as implied in some accounts (Hardt and Negri, 2000;Bello, 2006;Chang, 2008;Macartney, 2009Macartney, , 2011. We do agree that it would be simplifying too much a complex reality to put undue weight on the commonalities of European elites' interests.…”
Section: The Making Of Neoliberal Europementioning
confidence: 99%
“…The transnationalisation of capital thesis has been popular among students of globalisation (Carroll, 2010;Carroll et al, 2010;Robinson, 2004;Sklair, 2001), but it has also generated critical debate that has shown that it should not be exaggerated, as domestic and international elites are not homogenous and national dominant classes have not lost all ties to their home country, as implied in some accounts (Hardt and Negri, 2000;Bello, 2006;Chang, 2008;Macartney, 2009Macartney, , 2011. We do agree that it would be simplifying too much a complex reality to put undue weight on the commonalities of European elites' interests.…”
Section: The Making Of Neoliberal Europementioning
confidence: 99%
“…If neoliberalism-considered as both the contemporary period of capitalism [12] and as a complex ideology [24]-comprises beliefs and practices centered on market efficiency as the most efficient mechanism for regulating economic relations and renovating politico-economic strategies [25], its influence on agriculture is an idiosyncratic process that mingles free-market pressures and flexibilization approaches with renewed mechanisms of protectionism, trade barriers and labor movement restrictions [26]. Since the end of the 1980s, at least, the agenda of international development has tried to reconcile agricultural economic growth and the reduction of rural poverty with incentives and institutional adjustments aimed at increasing productivity and at promoting free trade.…”
Section: The Three Main Dimensions Of Agro-neoliberal Hegemonymentioning
confidence: 99%
“…Most importantly though, the UK financial sector was by far the largest in the EU and the City of London was the largest financial centre in Europe and the second largest in the world. Given the size of the financial sector – in particular when compared to the rest of the economy (Macartney, ) – British authorities had considerable subject‐specific expertise on matters related to finance and were regarded by many policy‐makers and stakeholders as providing state‐of‐the‐art regulation (Mügge, ). Moreover, British policy‐makers invested a considerable amount of technical and human resources in order to shape the regulatory debate in the EU (Posner and Véron, ).…”
Section: The Uk the Single Financial Market And Eu Financial Regulationmentioning
confidence: 99%